The Factor of Association of Diabetes Knowledge in Diabetes Mellitus type 2 patients - Monthida Sangruangake; Ponpimon Srisuwan; Piches Ruangsuksud; Solikhah Solikhah; Thiti Sungworawongpana (Universitas Ahmad Dahlan, 2022)
Background: T2DM is a chronic illness associated with numerous comorbidities and leads to chronic complications, resulting in high morbidity and mortality, rising health care costs. However, patients with this disease, through self-care, can significantly mitigate the risk, or delay the onset of these T2DM complications Objective: To investigate factors along with Diabetes Knowledge Method: A cross-sectional study was carried out among T2DM patients living in both rural and urban areas from the Central and Northeastern regions of Thailand were recruited from outpatient diabetes clinics of both community and university hospitals in both the Khon Kaen and Bangkok provinces of Thailand. Patients were sampled using a stratified sampling design where strata were based on locality (Province) - hospital size combinations. Firstly, we had translated all questionnaires from English to the local language then again back translated simultaneously. Then, the third step was to perform psychometric testing of the DK instrument Lastly, binary logistics mixed effect regression was used to investigate the clustering effect of the participant’s characteristic on this study. Results: After adjust for covariates derivate that age, KK and smaller hospitals, higher education, monthly income, underweight and overweight, DM treatment, and smoking nor alcohol where all found to be associated with various DK Conclusion: In future DK measurement is likely to provide valuable insights in to the epidemiology of diabetes self-management and may also be used to evaluate interventions to reduce poor self-care in T2DM patients, in turn, politically reducing the incidence of, and mortality from, type 2 diabetes mellitus complications.